Natural Nanoparticles for Drug Delivery: Proteomic Insights and Anticancer Potential of Doxorubicin-Loaded Avocado Exosomes - Dina Salem; Shaimaa Abdel-Ghany; Eman Mohamed; Nada F. Alahmady; Amany Alqosaibi; Ibtesam S. Al-Dhuayan; Mashal Meshal Alnamshan; Rebekka Arneth; Borros Arneth; Hussein Sabit (Pharmaceuticals, 2025)
Background: Exosomes have recently attracted significant attention for their potential in drug delivery. Plant-derived exosomes, in particular, may serve as direct anticancer agents due to their unique characteristics, including immunogenicity, biocompatibility, safety, cell-free nature, and nanoscale structure. Methods: This study characterizes Persea americana (avocado)-derived exosomes, exploring their anticancer properties, proteomic profile, and therapeutic potential. Results: Isolated exosomes exhibited a diameter of 99.58 ± 5.09 nm (non-loaded) and 151.2 ± 6.36 nm (doxorubicin (DOX)-loaded), with zeta potentials of −17 mV and −28 mV, respectively. Proteomic analysis identified 47 proteins, including conserved exosome markers (GAPDH, tubulin) and stress-response proteins (defensin, endochitinase). Functional enrichment revealed roles in photosynthesis, glycolysis, ATP synthesis, and transmembrane transport, supported by protein–protein interaction networks highlighting energy metabolism and cellular trafficking. DOX encapsulation efficiency was 18%, with sustained release (44.4% at 24 h). In vitro assays demonstrated reduced viability in breast cancer (MCF-7, T47D, 4T1) and endothelial (C166) cells, enhanced synergistically by DOX (Av+DOX). Gene expression analysis revealed cell-specific modulation: Av+DOX upregulated TP53 and STAT in T47D but suppressed both in 4T1/C166, suggesting context-dependent mechanisms. Conclusions: These findings underscore avocado exosomes as promising nanovehicles for drug delivery, combining biocompatibility, metabolic functionality, and tunable cytotoxicity. Their plant-derived origin offers a scalable, low-cost alternative to mammalian exosomes, with potential applications in oncology and targeted therapy. Further optimization of loading efficiency and in vivo validation are warranted to advance translational prospects.